Republic of Belarus - Basel Core Principles for Effective Banking Supervision Detailed Assessment of Compliance (Financial Sector Assessment Program, 2006)
This detailed assessment of observance with the basel core principles for effective banking supervision is the first external comprehensive assessment of the system of banking supervision in Belarus. The assessment of observance of each of the core principles follows a qualitative approach and is based on the core principles methodology document (October 1999). The assessment method consisted of examining the degree of observance of each of a principle's essential criteria and, where the assessors judged necessary, of the additional criteria. The assessment included a review of the relevant, legally non-binding instruments of the National Bank of the Republic of Belarus (NBRB) under the form of recommendations, the internal provisions of the NBRB, the licensing documents and the bank examination reports prepared by the NBRB, annual reports, the NBRB website, and other relevant material. The assessment is also based on the self-assessment prepared by the NBRB and discussions with staff in the banking supervision area, and with banks